Seleção de clones de canjerana (Cabralea canjerana) para a propagação por miniestaquia - Burin, Cláudia (2018)
Canjerana, Cabralea canjerana (Vell.) Mart., has problems for commercial production of seedlings, which justify searching for alternative techniques of propagation. Minicutting is an asexual propagation technique with satisfactory results and canjerana clones differ for adventitious rooting. So the objectives of this study were to define selection strategies and to identify canjerana clones for propagation by minicutting. The clonal mini-hedge of canjerana containing clones already established was composed in polyethylene trays containing coarse sand and flood fertigation. Sprouts were collected and quantified the total number of mini-cuttings per mini-stump, the percentages of survival, rooting and shooting, the number and length of roots and shoots and the number of rooted mini-cuttings per mini-stump. Data were submitted to analysis of variance and means were compared by the Scott-Knott test. Clones were clustered by non-hierarchical k-means method for the number of rooted mini-cuttings for each evaluation. Group means of each evaluation were compared by Student's t test for independent samples at 5% of error probability. Pearson correlation analysis was done among the studied traits. The identification of the best clones was done based upon the sum of ranks and estimated the genetic gain of selection. The selection of clones with the highest number of rooted mini-cuttings resulted in high values of indirect genetic gain of selection. In the development of canjerana clones for propagation by mini-cuttings, early selection should be applied to the number of rooted mini-cuttings during vegetative growth to extend the production season of canjerana plantlets. Selected clones have rooting competence during the whole year, which makes it possible to increase the production of canjerana plantlets.